Crimes against humanity : historical evolution and contemporary application - Bassiouni, M. Cherif , 1937- (Cambridge University Press, 2011)
"This book traces the evolution of crimes against humanity (CAH) and their application from the end of World War I to the present day, in terms of both historic legal analysis and subject-matter content. The first part of the book addresses general issues pertaining to the categorization of CAH in normative jurisprudential and doctrinal terms. This is followed by an analysis of the specific contents of CAH, describing its historic phases going through international criminal tribunals, mixed model tribunals, and the International Criminal Court. This includes both a normative and jurisprudential assessment as well as a review of doctrinal material commenting on all of the above. The book examines the general parts and defenses of the crime, along with the history and jurisprudence of both international and national prosecutions. For the first time, a list of all countries that have enacted national legislation specifically directed at CAH is collected, along with all of the national prosecutions that have occurred under national legislation up to 2010. The book constitutes a unique and comprehensive treatment of all legal and historical aspects pertaining to crimes against humanity in a single definitive volume"